In Situ Humoral Immunity to Vimentin in HLA-DRB1*03+ Patients With Pulmonary Sarcoidosis - Kinloch, Andrew J.; Kaiser, Ylva; Wolfgeher, Don; Ai, Junting; Eklund, Anders; Clark, Marcus R.; Grunewald, Johan (Frontiers in Immunology, 2018)
Vimentin has been implicated in pulmonary sarcoidosis as a T-cell autoantigen, particularly in the context of HLA-DRB1*03, the Vα2.3/Vβ22 T-cell receptor (TCR), and Löfgren’s syndrome. As vimentin is a known antigenic target in B-cell-mediated autoimmunity, we investigated in situ humoral anti-vimentin responses in pulmonary sarcoidosis and its relationship with HLA-DRB1*03. Sarcoid and healthy control (HC) lung biopsies were analysed by multi-colour confocal microscopy for B-cells, T-cells, proliferation and vimentin, and compared to tonsillectomy tissue. Bronchoalveolar lavage fluid (BALF) and serum from 48 sarcoidosis patients and 15 healthy volunteers were typed for HLA-DRB1*03 and titrated for antibodies to full-length vimentin, vimentin truncations, and total IgG and IgA by ELISA. Presence of extracellular vimentin in BALF was determined by mass spectrometry and T-cell populations measured by flow cytometry. Sarcoid lung samples, especially from HLA-DRB1*03+ patients, contained vimentin-rich tertiary lymphoid structures and corresponding BALF was highly enriched for both IgG and IgA anti-vimentin antibody (AVA) titres. Furthermore, sarcoidosis patient BALF AVA concentrations (expressed as arbitrary units per milligram of total immunoglobulin isotype) correlated with the percentage of CD4+ T-cells expressing the Vα2.3/Vβ22 TCR. BALF antibody reactivity to the vimentin N-terminus was most prominent in HCs, whereas reactivity to the C-terminus (VimC-term) was enriched in the sarcoid lung. Specifically, HLA-DRB1*03+ patient BALF contained higher concentrations of anti-VimC-term antibodies than BALF from both HCs and HLA-DRB1*03- patients. Consistent with the lung as a site of AVA production, the concentration of AVAs in BALF was dramatically higher than in matched serum samples. Overall, there was a poor correlation between BALF and serum AVA concentrations. Together, these studies reveal the presence of linked in situ recognition of vimentin by both T and B cells in HLA-DRB1*03+ sarcoidosis patients, associated with a selective humoral immune response to the vimentin C-terminus.